"Russia My History": A Hi-Tech Version of an Old History Textbook. Issue 1 (1st March 2021) - Konkka, Olga
Abstract: This article analyzes the presentation of the Second World War in the multimedia "history parks" of the Russian educational project "Russia My History." In these exhibition complexes, modern digital technologies offer visitors a "revolutionary" way to discover Russian history. The article first explores the history and conception of the Russia My History project, as a pedagogical tool, a digital museum, a historical narrative, and a response to current memory policies. Next, I focus on the exhibition dedicated to the Second World War (specifically, on its technical, visual, structural, lexical, and historical aspects) and assess the impact of the digitalization and commodification of history on the traditionally rigid official Russian memory of the war. I attempt to show that instead of exploiting digital technologies to develop new approaches to the history of the war, the exhibition neglects the potential of multimedia and provides a narrative close to the one used in Soviet and post-Soviet textbooks.